2005
DOI: 10.1107/s0907444904031798
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the F58W mutant of cytochromeb5: the mutation leads to multiple conformations and weakens stacking interactions

Abstract: Phe58 of cytochrome b5 is involved in stacking interactions with heme and the axial ligand His63. To elucidate the contribution of the stacking interactions to protein stability, the crystal structures of the F58Y and F58W mutants were determined at high resolution. The structure of the F58Y mutant is basically the same as that of the wild-type protein. However, the mutation from Phe58 to Trp58 leads to difficulty in growing single crystals and results in a space-group change; the six molecules in the asymmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…The crystal structure was further confirmed by XRD results (Figure 1d). The crystallinity of NaK(VO 3 ) 2 ‐V 2 O 5 has two Vanadium‐Based Oxides (NaK(VO 3 ) 2 : PDF#26‐1474 and V 2 O 5 : PDF#41‐1426) and is obviously lower than that in the literature, [ 13 ] which is related to the increased disorder of crystal structure caused by some vacancies, it can further accelerate the rapid transfer of electrons in the charging and discharging process due to the V 2 O 5 provide more space. X‐ray photoelectron spectroscopy (XPS) results confirmed that the electron cloud bias from electron‐rich V═O‐ and VOV‐ component to low binding energy field inducing the formation of built‐in electric field at the heterojunction interface (Figure 1e,f), which may accelerate the charge transfer dynamics at the heterogeneous interface.…”
Section: Resultsmentioning
confidence: 95%
“…The crystal structure was further confirmed by XRD results (Figure 1d). The crystallinity of NaK(VO 3 ) 2 ‐V 2 O 5 has two Vanadium‐Based Oxides (NaK(VO 3 ) 2 : PDF#26‐1474 and V 2 O 5 : PDF#41‐1426) and is obviously lower than that in the literature, [ 13 ] which is related to the increased disorder of crystal structure caused by some vacancies, it can further accelerate the rapid transfer of electrons in the charging and discharging process due to the V 2 O 5 provide more space. X‐ray photoelectron spectroscopy (XPS) results confirmed that the electron cloud bias from electron‐rich V═O‐ and VOV‐ component to low binding energy field inducing the formation of built‐in electric field at the heterojunction interface (Figure 1e,f), which may accelerate the charge transfer dynamics at the heterogeneous interface.…”
Section: Resultsmentioning
confidence: 95%